2021
DOI: 10.1161/jaha.120.019240
|View full text |Cite
|
Sign up to set email alerts
|

Beta‐Blocker Use Is Associated With Prevention of Left Ventricular Remodeling in Recovered Dilated Cardiomyopathy

Abstract: Background Withdrawal of optimal medical therapy has been reported to relapse cardiac dysfunction in patients with dilated cardiomyopathy (DCM) whose cardiac function had improved. However, it is unknown whether beta‐blockers can prevent deterioration of cardiac function in those patients. We examined the effect of beta‐blockers on left ventricular ejection fraction (LVEF) in recovered DCM. Methods and Results We analyzed the clinical per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 32 publications
0
23
1
Order By: Relevance
“…17, 18 In addition, the use of β-blockers was associated with the prevention of LV dysfunction in reversed DCM. 16 LV reverse remodeling is a surrogate endpoint in HF clinical trials. 21 Previous national surveys in Japan in 2002 revealed that the prescription rates of β-blockers and ACEi for DCM were 41% and 65%, respectively, 11,12 indicating insufficient OMT for DCM patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17, 18 In addition, the use of β-blockers was associated with the prevention of LV dysfunction in reversed DCM. 16 LV reverse remodeling is a surrogate endpoint in HF clinical trials. 21 Previous national surveys in Japan in 2002 revealed that the prescription rates of β-blockers and ACEi for DCM were 41% and 65%, respectively, 11,12 indicating insufficient OMT for DCM patients.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we have used the Clinical Personal Records to report on the clinical features of DCM patients and routine practices, as well as the effectiveness of β-blockers and ACEi/ARB on LV reverse remodeling in DCM. [15][16][17][18] This database is the largest and most reliable for investigations into clinical information regarding DCM in Japan. The aim of the present study was to describe temporal trends in the clinical characteristics and medical treatment of DCM in Japan using the nationwide Clinical Personal Records database.…”
Section: Ethics Statementmentioning
confidence: 99%
“… 10 Many clinical studies also show that BB could effectively suppress the progression of left ventricular remodelling, 22 , 23 which directly contributes to the improvement of left ventricular function. 17 Sahoo et al . have also reported that the usage of BB is able to improve left ventricular parameters in a group of patients with rheumatic mitral regurgitation.…”
Section: Discussionmentioning
confidence: 99%
“…Although our data did not include any parameters of cardiac structure or function other than LVEF, these results strongly suggest that recovered LV function alone is not a clinically useful indicator that may advise discontinuation of HF medications, even in post-AMI HFresEF patients 32 . Also, these observations implied the importance of regular surveillance and continuation of GDMT including RAASi in HFresEF patients 35 . Future studies should determine which component of GDMT is more critical to prevent relapse, and also should focus on elucidating the characteristics that distinguish remission from permanent recovery in post-AMI HFresEF patients.…”
Section: Continuation Of Gdmt In Post-ami Patients With Hfresef In Co...mentioning
confidence: 96%